Data Privacy Management and Autonomous Spontaneous Security 4th International Workshop, DPM 2009 and Second International Workshop, SETOP 2009, St. Malo, France, September 24-25, 2009, Revised Selected Papers - Garcia-Alfaro, Joaquin; Navarro-Arribas, Guillermo; Cuppens-Boulahia, Nora.; Roudier, Yves.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the two international workshops DPM 2009, the 4th International Workshop on Data Privacy Management, and SETOP 2009, the Second International Workshop on Autonomous and Spontaneous Security, collocated with the ESORICS 2009 symposium in St. Malo, France, in September 2009. The 8 revised full papers for DPM 2009, selected from 23 submissions, presented together with two keynote lectures are accompanied by 9 revised full papers of SETOP 2009; all papers were carefully reviewed and selected for inclusion in the book. The DPM 2009 papers cover topics such as privacy in service oriented architectures, privacy-preserving mechanisms, crossmatching and indistinguishability techniques, privacy policies, and disclosure of information. The SETOP 2009 papers address all current issues within the sope of security policies, identification and privacy, as well as security mechanisms.
Keynote Talks -- The UNESCO Chair in Data Privacy Research in Vehicular Networks -- Privacy Management for Global Organizations -- Data Privacy Management -- Obligation Language and Framework to Enable Privacy-Aware SOA -- Distributed Privacy-Preserving Methods for Statistical Disclosure Control -- Towards a Privacy-Preserving National Identity Card -- Using SAT-Solvers to Compute Inference-Proof Database Instances -- A Quantitative Analysis of Indistinguishability for a Continuous Domain Biometric Cryptosystem -- A Spatial Cloaking Framework Based on Range Search for Nearest Neighbor Search -- Visualizing Privacy Implications of Access Control Policies in Social Network Systems -- Contextual Privacy Management in Extended Role Based Access Control Model -- Autonomous and Spontaneous Security -- Dynamic Security Rules for Geo Data -- Medical Image Integrity Control Combining Digital Signature and Lossless Watermarking -- ASRBAC: A Security Administration Model for Mobile Autonomic Networks (MAutoNets) -- Untraceable Tags Based on Mild Assumptions -- Security Threat Mitigation Trends in Low-Cost RFID Systems -- An Effective TCP/IP Fingerprinting Technique Based on Strange Attractors Classification -- DDoS Defense Mechanisms: A New Taxonomy -- RDyMASS: Reliable and Dynamic Enforcement of Security Policies for Mobile Agent Systems -- Achieving Life-Cycle Compliance of Service-Oriented Architectures: Open Issues and Challenges.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computers -- Law and legislation; Information Systems; Computer Science; Systems and Data Security; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Legal Aspects of Computing; Computers and Society